2014
DOI: 10.1007/s13201-014-0205-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the characteristic of nutrients, total metals, and fecal coliform in Sibu Laut River, Sarawak, Malaysia

Abstract: The concentrations of nutrients (nitrogen and phosphorus), total metals, and fecal coliform (FC) coupling with chlorophyll-a (chl-a), 5-day biochemical oxygen demand (BOD 5 ) and other general environmental parameters were evaluated at the sub-surface and near-bottom water columns of 13 stations in the Sibu Laut River during low and high slack waters. The results indicated that inorganic nitrogen (mainly nitrate) was the primary form of nitrogen whereas organic phosphorus was the major form of phosphorus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…The negative correlation between salinity and nitrogen and positive correlation between pH and nitrogen indicated the contribution of riverine nitrogen source to the Sarawak coastal water. Reference [7] demonstrated that the Sibu Laut River contained high NO 3 − -N concentration which is in agreement with the NO 3 − -N concentration in the coastal water. In addition, the high DO content in coastal water also accelerates the decomposition and nitrification process where organic content was converted to the end product of NO 3 − -N. The present study demonstrated that Sarawak nearbottom coastal water was rich in total phosphorus where it was categorized from mesotrophic to hypertrophic status.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The negative correlation between salinity and nitrogen and positive correlation between pH and nitrogen indicated the contribution of riverine nitrogen source to the Sarawak coastal water. Reference [7] demonstrated that the Sibu Laut River contained high NO 3 − -N concentration which is in agreement with the NO 3 − -N concentration in the coastal water. In addition, the high DO content in coastal water also accelerates the decomposition and nitrification process where organic content was converted to the end product of NO 3 − -N. The present study demonstrated that Sarawak nearbottom coastal water was rich in total phosphorus where it was categorized from mesotrophic to hypertrophic status.…”
Section: Discussionmentioning
confidence: 53%
“…Station 7 was located near the Sibu Laut River which forms the western boundary of the Kuching Wetland National Park. Shrimp farms and villages were located along the river which contributed substantial organic matter to the river and subsequently the coastal area [7,34]. Coastal water quality at other stations was relatively good and mostly complied with the MWQS, except for NO 3 − -N where all stations violated the MWQS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations